Experimental statistics - Natrella, Mary Gibbons (Dover Publications, 2005)
This highly regarded handbook is perfect for those seeking engineering information and quantitative data for designing, developing, constructing, and testing equipment. Topics include characterizing and comparing the measured performance of a material, product, or process; general considerations in planning experiments; statistical techniques for analyzing extreme-value data; and more. 1966 edition. Index. Includes 52 figures and 76 tables.
Originally published: Washington, D.C. : U.S. Dept. of Commerce, National Bureau of Standards, 1963, in series: National Bureau of Standards handbook ; 91.
Keywords: Mathematical statistics -- Handbooks, manuals, etc.; Experimental design -- Handbooks, manuals, etc.; elektronické knihy; electronic books